Integrated Education Approach in Islamic Higher Education Institutions in Malaysia: Challenges and Opportunities - Muslihah Mazlan; Najwa Alyaa Abd Wakil; Mohd Aderi Che Noh; Muhammad Haris Riyaldi (Universiti Sultan Azlan Shah, 2026)
Indexed by SCOPUS